Therapeutic Potential of Natural Acetogenins: Extraction Techniques, Pharmacological Activities, and Future Applications - Yabansabra, Yuliana R.; Abulais, Diana; Simaremare, Eva (Jurusan Biologi FMIPA Universitas Cenderawasih, 2025)
Acetogenins, a unique class of secondary metabolites primarily found in the Annonaceae family, exhibit remarkable pharmacological properties, particularly as potent cytotoxic and anticancer agents. This systematic review synthesizes recent advancements in acetogenin research, focusing on extraction methodologies, biological activities, and therapeutic applications. A structured literature search spanning 2010–2024 was conducted across PubMed, Scopus, Web of Science, and Google Scholar, adhering to PRISMA guidelines. The findings highlight the efficacy of acetogenins in inhibiting cancer cell proliferation, particularly in breast, colorectal, and brain cancers, through mitochondrial inhibition and apoptosis induction. Recent innovations, including ultrasonic-assisted extraction and nanoparticle-based formulations, have significantly improved bioavailability and therapeutic outcomes. Despite these promising developments, challenges such as low solubility, potential neurotoxicity, and limited clinical validation persist. Future research should prioritize the optimization of drug delivery systems and in-depth clinical trials to establish acetogenins as next-generation natural anticancer agents